The Baby-Sitters Club: Kristy's Great Idea - Book 1 - Telgemeier, Raina; Martin, Ann M. 1955- (New York, NY Graphix, an imprint of Scholastic, 2015)
Follows the adventures of Kristy and the other members of the Baby-sitters Club as they deal with crank calls, uncontrollable two-year-olds, wild pets, and parents who do not always tell the truth.
Keywords: Babysitters -- Juvenile fiction; Clubs -- Juvenile fiction